The effect of laparoscopy courses in laparoscopy practice after urology resident training: A questionnaire-based observational study - Özmerdiven, Gökhun; Kaygısız, Onur; Çiçek, Çağatay; Günseren, Kadir Ömür; Vuruşkan, Hakan (Journal of Surgery and Medicine, 2019)
Aim: Laparoscopy is an important part of surgical training. Laparoscopy courses are organized to increase competence of laparoscopy. This aim of this paper is to evaluate the laparoscopic surgery competence of Turkish urologists and the effectiveness of laparoscopy courses. Methods: In 2014, an online survey consisting of 11 questions was sent to 180 urologists via e-mail, among which 78 responded. The survey questions aimed at gathering information about where the urologists worked, their laparoscopic surgical experience, how long they attended laparoscopy courses, and whether they considered themselves to be competent in laparoscopic surgeries. Results: 41.2% of the respondents who considered themselves to be competent in laparoscopy and 84.1% of those who did not, stated that they wanted to attend laparoscopy courses (P<0.001). 100% of the respondents who could perform Level-1 laparoscopy surgeries stated that they did not consider themselves to be competent and wanted to receive laparoscopic training (P<0.001). 54.9% of those who did not receive laparoscopy training during their residency and 48.1% of those who received training during residency stated that they attended courses in the past. All respondents who attended long-term courses and 73.6% of those who attended short-term courses could perform laparoscopic surgeries (P<0.001). It was also determined those who attended long-term courses could perform complicated laparoscopic surgeries (P<0.001). Conclusion: This study revealed that the courses contributed a lot to laparoscopic surgical competence after residency. The study stresses that if the urologists who did not receive laparoscopy training during their residency attend long-term courses, they can increase their competence in laparoscopy.